The Roles of Determinants of Self-employment: A Mediation of Entrepreneurial Motivation in Bauchi State, Nigeria - Adamu, Muhammad; Abdu Shakur, Mahani Bint Mohammad (International Journal of Accounting & Finance Review, 2017)
Today, the problem of unemployment has been a global issue, even among the developed nations, and especially the developing nations. For this reason, the need for employment generation becomes desirably indispensable. The aim of this research work is to examine the essential roles that entrepreneurial traits and economic incentive factors would play with the mediation of entrepreneurial motivation for an effective self-employment start-up accomplishment. Self-employment has long been recognized as an alternative for individuals to become self-reliant. Thus, this is expected brings about a reduction in poverty level, improved living standard as well as to earn more income and have a better career as a means of sustenance for potential entrepreneurs. For this purpose, it is essentially important to make an examination of certain vital factors, which may constitute the basics necessary to effect self-employment particularly from the context of entrepreneurial traits and economic incentive factors that would motivate the potential entrepreneurs to achieve success in self-employment start-up.